Visual assessment of colorectal flat and depressed lesions by using narrow band imaging - Nakamura, Hiroshi; Ikematsu, Hiroaki; Osera, Shozo; Ito, Renma; Sato, Daiki; Minamide, Tatsunori; Okamoto, Naoki; Yamamoto, Yoichi; Hombu, Takuya; Takashima, Kenji; Nakajo, Keiichiro; Kadota, Tomohiro; Yoda, Yusuke; Hori, Keisuke; Oono, Yasuhiro; Yano, Tomonori (Endoscopy International Open, 2017)
Background and study aims Visual assessment of laterally spreading tumors non-granular type (LST-NG) and depressed lesions by narrow band imaging (NBI) without magnification has not been studied. We investigated the role of non-magnifying NBI in detecting LST-NG and type IIc lesions on colonoscopy.Patients and methods This retrospective study examined consecutive patients diagnosed as having LST-NG and/or type IIc lesions in our hospital between August 2011 and July 2013. These lesions were classified as “Brownish area (BA),” “Brown only in the margins (O-ring sign),” “Same color as the normal mucosa (SC),” and “Whitish area (WA)” based on their appearance on non-magnifying NBI, and their appearance were compared with their histopathological findings.Results A total of 18 type IIc and 180 LST-NG lesions were analyzed. Among the type IIc lesions, 5 (28 %), 12 (67 %), and 1 (5 %) were classified as BA, O-ring sign, and SC, respectively. Among the LST-NG lesions, 126 (70 %), 26 (14 %), and 28 lesions (16 %) were classified as BA, O-ring sign, and SC, respectively. The IIc lesions were found to have 1 lesion (20 %) with high-grade dysplasia (HGD) in the BA, and 2 lesions (17 %) with invasive cancer (IC) in the O-ring sign group. Among the LST-NG lesions, 27 (21 %) were found to have IC and 49 (39 %), HGD in the BA group; 8 lesions (31 %) had IC and 4 (15 %) had HGD in the O-ring sign group; and 1 lesion (4 %) had IC and 4 (14 %) had HGD in the SC group.Conclusions Most flat and depressed colorectal lesions were seen on non-magnifying NBI as brown lesions with the exception of some flat lesions that were indistinguishable in color from the adjacent normal mucosa. Some of these flat lesions were also found to have HGD or IC.